The Church and Humanity: The Life and Work of George Bell, 1883–1958. Edited by Andrew Chandler - Gorringe, Timothy (The journal of theological studies, 2013)
The twelve essays collected here began life in a series of lectures to mark the fiftieth anniversary of George Bell’s death in 1958. Five of them, in one way or another, as might be expected, look at Bell’s connections with Germany. Andrew Chandler sets the scene with a brief biography which begins by reminding us what an absolutely different world Bell inhabited as a young man. Well, not absolutely different perhaps. Les Desmoiselles d’Avignon and The Rite of Spring both appeared before the First World War and both remain startlingly ‘modern’. By the side of these the Masefield play which Bell commissioned for Canterbury looks extremely lame, though Bell was also a friend of T. S. Eliot and had a hand in commissioning Murder in the Cathedral.